2021
DOI: 10.3390/ani11092701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selenium Auricularia cornea Culture Supplementation on Growth Performance, Antioxidant Status, Tissue Selenium Concentration and Meat Quality in Growing-Finishing Pigs

Abstract: Selenium Auricularia cornea culture (SAC) is a new source of organic selenium. Two experiments were conducted to determine the available energy of SAC fed to pigs and to evaluate the effects of dietary SAC supplementation on growth performance, serum biochemical profiles, fecal short chain fatty acids (SCFA), meat quality, tissue selenium concentration, and oxidative stability of fresh meat in growing-finishing pigs. In Experiment (Exp.) 1, 12 barrows with average body weight (BW) of 42.40 ± 5.30 kg were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Pork from the O-300 and O-100 diet had a higher cohesiveness, hardness, gumminess and resilience value than from the O-0 diet ( Table 5 ). Previously, researchers indicated that there was a strong relationship between muscle fibers type and the sensory traits of “cohesiveness” and “resilience” in pork [ 28 , 29 , 30 , 31 ]. The type of muscle fiber is determined by the expression of genes, such as MyHC-I , MyHC-IIa etc.…”
Section: Discussionmentioning
confidence: 99%
“…Pork from the O-300 and O-100 diet had a higher cohesiveness, hardness, gumminess and resilience value than from the O-0 diet ( Table 5 ). Previously, researchers indicated that there was a strong relationship between muscle fibers type and the sensory traits of “cohesiveness” and “resilience” in pork [ 28 , 29 , 30 , 31 ]. The type of muscle fiber is determined by the expression of genes, such as MyHC-I , MyHC-IIa etc.…”
Section: Discussionmentioning
confidence: 99%